Bloom's Taxonomy Theory in the Pedagogical Value of Domyak Art: An Ethnopedagogical Perspective - Anggy Giri Prawiyogi; Retno Dwimarwati; Suhendi Afryanto; Yulistina Nur DS; Andes Safarandes Asmara (Journal of Innovation in Educational and Cultural Research, 2023)
Domyak art is an art that has two functions, namely, as a means of ritual and as a means of entertainment. This study aims to examine the inherited local wisdom values contained in domyak art. An Ethno pedagogy-based qualitative research method was used to describe the series of implementations. Ethno pedagogy is an educational approach that focuses on local wisdom and the importance of human relations through an educational perspective. This research focuses on Domyak art in Pasirangin Village, Darangdan, Purwakarta Regency, West Java. In Domyak art, some codes contain the use of signs which are then analyzed through Bloom's taxonomy theory to see the educational values contained therein. The results of this research find pedagogical values contained in Bloom's theory, namely cognitive, a mindset; effective, an attitude; and psychomotor, an action. Domyak itself means (ngadogdog and rampayak) playing dogdog music with dance to ask for rain in the dry season. There are values of sauyunan, silih asah silih asih slih asuh, sarendeuk saigel, ulah pahiri-hiri ulah pa aing-aing, and other attitudes that can be applied in socialising with the community. This research contributes to raising the pedagogical values in Domyak art connected with Bloom's taxonomy theory.